Clinico-epidemiologichesky aspects of the mixed tick-borne infections in the endemic region - E. S. Aleshkovskaya; N. A. Blagov; V. A. Bazunova (Журнал инфектологии)
Detection of clinico-epidemiological features of the mixed tick-borne infections – tick-borne Lyme disease and a human granulocytic anaplasmosis was the purpose of the conducted research. During the spring – summer period 146 patients with tick-borne borreliosis were surveyed. As a result at 45 (30,82%) patients authentically diagnosed the mixed tick-borne infection. Features of clinical manifestations of a mixed tick-borne infection revealed: catarrhal phenomena (20%), liver defeats (33%), nephros (31, 7%), frequent secondary erythems (20%). Changes in haemogram defined: thrombocytopenia (42,2%), anemia (20%), leukopenia (13,3%).